The mega peripheral metropolis: towards a comprehensive explanation - Jucá, Antonio (Ciência & Trópico, 2019)
This paper presents a comprehensive approach for the urbanization process, firstly discussing urban growth in order to perceive how a set of forces of urbanization work together. The analysis presents economic crises and roles of states as central elements through an argumentative discourse, targeting the exam of urban growth in periphery emerging countries. This is an attempt to explain super urban agglomerations in these countries, which often absorb most of the domestic and foreign investments, creating a cycle of growth, either economic or in terms of population, apparently with no control. Yet theoretically, this thinking also discusses possible scenarios of the process over networks of cities in these countries, defining and confining the concept of urban network, as well as other concepts in a critical way.